STRATEGI ADAPTASI PETANI RAKYAT DALAM MENGATASI PENURUNAN HARGA KELAPA SAWIT DI DESA ESPETIGA KECAMATAN PENINJAUAN KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
Adaptation strategy of smallholder farmers to overcome the decrease of oil palm price in Espetiga village, District of Ogan Komering Ulu District. The study was conducted intentionally by a simple random survey method. With farmer's example 30 farmers, farmer's income before price decrease Rp 8.612.147 at the time of price reduction Rp 4.704.747 with farmer adaptation strategy 15 farmers choose active strategy, 5 farmers choose passive strategy, and 10 farmers choose network strategy. Keywords : active strategy, passive strategy